The Impact of Maternal Preeclampsia and Hyperglycemia on the Cardiovascular Health of the Offspring: A Systematic Review and Meta-analysis - Hoodbhoy, Zahra; Mohammed, Nuruddin; Nathani, Karim Rizwan; Sattar, Saima; Chowdhury, Devyani; Maskatia, Shiraz; Tierney, Seda; Hasan, Babar; Das, Jai K. (American Journal of Perinatology, 2021)
Objectives The objective of this review was to assess the impact of maternal preeclampsia or hyperglycemia on the body composition and cardiovascular health in the offspring.Study Design We conducted a systematic review utilizing PubMed, EBSCO, CINAHLPlus, Cochrane Library, and Web of Science to include all studies assessing the impact of preeclampsia/eclampsia and/or gestational/pregestational diabetes mellitus on the health of the offspring (children <10 years of age). The health measures included anthropometry, cardiac dimensions and function, and vascular function. We performed a meta-analysis using Review Manager software and computed net risk ratio (RR) with 95% confidence interval (CI) for dichotomous data and mean difference (MD) with 95% CI for continuous data.Results There were 6,376 studies in total, of which 45 were included in the review and 40 in the meta-analysis. The results demonstrated higher birth weight (MD: 0.12 kg; 95% CI: 0.06–0.18) and systolic and diastolic blood pressure (BP; MD: 5.98 mm Hg; 95% CI: 5.64–6.32 and MD: 3.27 mm Hg; 95% CI: 0.65–5.89, respectively) in the offspring of mothers with gestational diabetes compared to controls. In contrast, the offspring of mothers with preeclampsia had lower birth weight (MD: −0.41 kg; 95% CI: −0.7 to −0.11); however, they had increased systolic (MD: 2.2 mm Hg; 95% CI: 1.28–3.12) and diastolic BP (MD: 1.41 mm Hg; 95% CI: 0.3–2.52) compared to controls. There is lack of data to conduct a meta-analysis of cardiac morphology, functional, and vascular imaging parameters.Conclusion These findings suggest that the in-utero milieu can have a permanent impact on the body composition and vascular health of the offspring. Future work warrants multicenter prospective studies to understand the mechanism and the actual effect of exposure to maternal hyperglycemia and high BP on the cardiovascular health of the offspring and long-term outcomes.Key Points
Keywords: hyperglycemia; preeclampsia; in-utero exposure; cardiovascular health; children; vascular health